Compositional Variation of Amphiboles During Magma Mixing: A Case Study of Huangyangshan A-Type Granite in Kalamaili Metallogenic Belt, East Junggar, China - Ye, Chenyang; Feng, Yonggang; Lei, Ruxiong; Yang, Gaoxue (Frontiers in Earth Science, 2021)
The Huangyangshan A-type granitic pluton, distributed along the thrust fault in the Kalamaili region of East Junggar, Xinjiang, China, consists of alkaline granite containing abundant dioritic enclaves that formed via magma mixing. Both the host granite and the enclaves contain sodic amphiboles. The textural evidence indicates that amphiboles crystallized as a magmatic phase in both units. We determined major and trace element contents of amphiboles from both units to investigate the compositional variation of the amphiboles during the magma mixing process. The results show that cations of W- and C-site are influenced by chemical compositions of the magma whereas cations of A-, B- and T-site and Al3+ are controlled by crystal structure. Therefore, the variations of W- and C-site cations can reflect magma evolution. The core and rim of the amphiboles show similar trace element patterns, which also suggests that the amphiboles are late-stage phases. Furthermore, the amphibole-only thermometers yield reasonable estimates that are consistent with petrographic evidence. However, thermometers based on partition coefficients and all the currently available amphibole-based barometers that rely on Al contents or DAl cannot be applied to Fe-rich and Al-poor amphiboles.